Understanding the Heterogeneity of Labor and Delivery Units: Using Design Thinking Methodology to Assess Environmental Factors that Contribute to Safety in Childbirth - Sherman, Jules P.; Hedli, Laura C.; Kristensen-Cabrera, Alexandria I.; Lipman, Steven S.; Schwandt, Doug; Lee, Henry C.; Sie, Lillian; Halamek, Louis P.; Austin, Naola S.; Safety Learning Laboratory for Neonatal and Maternal Care (American Journal of Perinatology, 2020)
Objective There is limited research exploring the relationship between design and patient safety outcomes, especially in maternal and neonatal care. We employed design thinking methodology to understand how the design of labor and delivery units impacts safety and identified spaces and systems where improvements are needed.Study Design Site visits were conducted at 10 labor and delivery units in California. A multidisciplinary team collected data through observations, measurements, and clinician interviews. In parallel, research was conducted regarding current standards and codes for building new hospitals.Results Designs of labor and delivery units are heterogeneous, lacking in consistency regarding environmental factors that may impact safety and outcomes. Building codes do not take into consideration workflow, human factors, and patient and clinician experience. Attitude of hospital staff may contribute to improving safety through design. Three areas in need of improvement and actionable through design emerged: (1) blood availability for hemorrhage management, (2) appropriate space for neonatal resuscitation, and (3) restocking and organization methods of equipment and supplies.Conclusion Design thinking could be implemented at various stages of health care facility building projects and during retrofits of existing units. Through this approach, we may be able to improve hospital systems and environmental factors.
Keywords: design thinking; neonatology; obstetrics; labor and delivery; hospital design; environmental factors